Optimal control for the UAV’s lateral motion with incomplete measurements of the state vector components - Тунік, А. А.; Галагуз, Т. А.; Комнацька, М. М.; Білий, Т. А. (Problems of Informatization and Control, 2005)
The synthesis of the optimal control system for the small UAV’s lateral motion with incomplete measurements of the UAV’s state vector components. Optimal control is achieved with application of the Luenberger observer along with the optimal Iqr-controller